2022
DOI: 10.1088/1475-7516/2022/04/021
|View full text |Cite
|
Sign up to set email alerts
|

The effective field theory of large-scale structure and multi-tracer

Abstract: We study the performance of the perturbative bias expansion when combined with the multi-tracer technique, and their impact on the extraction of cosmological parameters. We consider two populations of tracers of large-scale structure and perform a series of Markov chain Monte Carlo analysis for those two tracers separately. The constraints in ω cdm and h using multi-tracer are less biased and approximately 60% better than those obtained for a single tracer. The multi-tracer approach also prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 135 publications
3
20
0
Order By: Relevance
“…In a high dimensional parameter space such as ours this involves many likelihood evaluations. In order to minimize the computing resources we require, we replace the model calculations involved in the likelihood computation with an emulator based on Taylor series expansions [22,24,[106][107][108]. This reduces the time-perlikelihood-evaluation to tens of milliseconds.…”
Section: Emulatorsmentioning
confidence: 99%
“…In a high dimensional parameter space such as ours this involves many likelihood evaluations. In order to minimize the computing resources we require, we replace the model calculations involved in the likelihood computation with an emulator based on Taylor series expansions [22,24,[106][107][108]. This reduces the time-perlikelihood-evaluation to tens of milliseconds.…”
Section: Emulatorsmentioning
confidence: 99%
“…When having two tracers A and B, their auto-spectra will be the same as those defined in the previous section. Nevertheless, the cross-power spectrum will have a different form [47]:…”
Section: Multi-tracer (Mt)mentioning
confidence: 99%
“…As we have motivated in [47], the gains of doing multi-tracer go beyond cosmic variance cancellation in linear scales. We have shown that a real-space FS analysis of MT combined with EFTofLSS outperforms the usual single-tracer (ST) approach, improving the constraints on cosmological parameters with error bars approximately 60% smaller relative to ST.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a full expression for [35]. For a generalization of the largescale bias expansion to more tracers, see [54]. The two last terms correspond respectively to a term proportional to ∇ 2 δδ ∼ k 2 P lin and the stochastic contribution proportional to k 0 and k 2 .…”
Section: The Large-scale Bias Expansionmentioning
confidence: 99%